Giant superficial angiomyxoma of the male perineum: A case report - Yan, Sheng; Zou, Yuhua; Liao, Xinzhi; Zhong, Cunzhi; Liu, Shengyin; Huang, Sigen; Zou, Junrong; Liu, Quanliang (Frontiers in Surgery, 2023)
Background：Superficial angiomyxoma (SA) is a rare benign tumor occurring in the superficial dermis or subcutaneous.It often occurs in the skin or subcutaneous of trunk, neck or limbs, and grows slowly. Generally, the diameter of the tumor is less than 5cm. Giant SA of the perineum in men is very rare. We detailed the diagnosis and treatment of male patients with perineal SA and performed a literature review. Case Description: We report a case of a 42-year-old male patient. He was admitted to the hospital with a perineal mass found for more than 1 year. The pelvic contrast-enhanced computed tomography (CE-CT) in our hospital suggests that a round slightly hypointense foci of about 6.0×8.6×4.5 cm in size with still clear borders was seen below the penile corpus cavernosum in the perineum. We performed a perineal mass excision under continuous epidural anesthesia. Postoperative pathology report diagnosing perineal SA. To May 2022 (27 months), no recurrence at follow-up. Conclusions: Perineal SA is rare and should be combined with patient history and imaging to ensure complete excision of the mass margins, and adherence to long-term postoperative follow-up is the key to the cure of this case.